Estrategia didáctica "Aprendo Jugando" y su influencia en el aprendizaje de la multiplicación y división en los estudiantes del IV ciclo, en el Área Lógico Matemática de educación primaria de la Institución Educativa José Carlos Mariátegui del distrito de Rioja en el año 2008 - Castro Gonzales, Joselito (2009)
The qualified investigation(research) didactic strategy “I Learn playing" and his(her,your) influence in the learning of the multiplication and division in the students of the Cycle IV, in the area logically mathematics of primary education of the Educational lnstitution Jose Carlos Mariátegui of the district of Rioja in the year 2008, it(he,she) has had far aim(lens) demonstrate that the application of the strategy "I Learn Playing" there influences in the learning of the multiplication and division in the students of the Cycle IV, in the area Logically Mathematics of Primary Education of the Educational lnstitution Jose Carlos Mariátegui of the district of Rioja. The didactic strategy " 1 Learn playing " systematized by means of the presentation, organization and development, orientated by the theory of the active learning, by the theory of the significant learning and by the theory of the cooperative learning, it has been allowed hipotetizar that The didactic strategy “I Learn playing”., There will influence significantly in the learning of the multiplication and division in the students of the Cycle IV, in the area Logically Mathematics of Primary Education of the Educational lnstitution Jose Carlos Mariátegui of the district of Rioja. To verify the results obtained of 24 students, on having administered the test(proof) before and after the application of the strategy, the design has been in use of contrastación pre experimental with pre and posttries. The comparison of averages of paired measures has allowed to establish that The didactic strategy "I Learn playing", there influences significantly in the learning of the multiplication and division in the students of the Cycle IV, in the area Logically Mathematics of Primary Education of the Educational lnstitution Jose Carlos Mariátegui of the district of Rioja.